Terrorisme ou guerre de libération ? Lecture critique du conflit israélo-palestinien dans The Promise de Peter Kosminsky (Channel Four, 2011) - Maggy Hary (TV Series, 2016)
Since Peter Kosminsky started his career as a film director, war has featured as a prominent theme in his work, whether in documentaries (The Falklands War: the Untold Story, Yorkshire Television, 1987) or dramas (Warriors, BBC One, 1999). The Promise (Channel 4, 2011), which deals with the history of the Israeli-Arab conflict, reflects Kosminsky’s enduring engagement with this topic. More than a simple history series aiming to faithfully depict past events, The Promise focuses on the violence that marked the birth of the Jewish state in order to draw parallels with today’s confrontation between Israel and the Palestinians. Such an approach allows Kosminsky to provide a critical and eminently controversial interpretation of a conflict which seems doomed to go on forever. Yet, by enlisting the viewer’s sympathy for all the characters that embody this great historical narrative, whatever their political leanings may be, Kosminsky portrays a thorny situation in a balanced and sensitive way, without reducing it to Manichean simplifications.